Attenuation of Brain Response to VEGF-mediated Angiogenesis and Neurogenesis in Aged Mice - Gao, Peng (2009)
BACKGROUND AND PURPOSE: Alterations of neuro-angiogenic response play important roles in the development of aging-related neurodisorders, and affect gene-based therapies. We tested brain response to vascular endothelial growth factor (VEGF) in aged mice. METHODS: AAV-VEGF, an adeno-associated viral vector expressing VEGF, was injected into the brain of 3-, 12- and, 24-month old mice. AAV-LacZ-injected mice were used as control (n=6). Before euthanization at 6 weeks after vector injection, the mice were intraperitoneally injected with BrdU for 3 consecutive days. The vascular density and the number of neuroprogenitors were analyzed. RESULTS: Injection of AAV-VEGF increased the vascular density in the brain of 3-, 12-and 24-month old mice by 22±7% (AAV-VEGF: 320±15 per 10X field vs. AAV-LacZ: 263±8, p<0.05), 20%±8 (AAV-VEGF: 300±9 vs. AAV-LacZ: 250±11, p<0.05), and 7±16% (AAV-VEGF: 257±27 vs. AAV-LacZ: 236±13, p=0.283), respectively. There were more VEGF receptor positive neuroprogenitors in the subventricular zone of AAV-VEGF injected 3- (22±2) and 12-month old mice (21±5) than that of 24-month old mice (7±1). More BrdU positive endothelial cells and neuroprogenitors were detected around the injection site and SVZ of 3- (13±4) and 12-month old mice (14±5) than that of 24-month old mice (1±1). VEGF receptor 2 was upregulated in AAV-VEGF-injected brains of 3- and 12-month old mice, but not in 24-month old mice. CONCLUSION: The angiogenic and neurogenic response to VEGF stimulation is attenuated in the aged mouse brain, which may be due to reduced VEGF receptor activity.